Cortical aneurysms of the middle cerebral artery: A review of the literature - Ricci, Alessandro (Surg Neurol Int, 2017)
BACKGROUND: Middle cerebral artery (MCA) aneurysms constitute from 18–40% of all intracranial aneurysms. They are mainly found in the proximal and bifurcation tracts and only in the 1.1-1.7% of cases they are located in the distal segment. The authors report a case of a ruptured saccular cortical MCA aneurysm with unknown etiology. CASE DESCRIPTION: A 53-year-old female was admitted with a sudden severe headache, nausea, vomiting, and a slight left hemiparesis. The computed tomography (CT) scan showed subarachnoid hemorrhage (SAH) in the left sylvian fissure and intracerebral hemorrhage (ICH) in the left posterior parietal area. The CT angiography (CTA) reconstructed with 3D imaging showed a small saccular aneurysm in the M4 segment in proximity of the angular area. A left parieto-temporal craniotomy was performed, the aneurysm was clipped and the ICH evacuated. The motor deficit was progressively recovered. At 3-month follow-up examination, the patient was asymptomatic and feeling well. CONCLUSIONS: In our opinion, surgery is the best choice for the treatment of ruptured M4 aneurysms with ICH, because it allows to evacuate the hematoma and to exclude the aneurysm from the intracranial circulation. In addition, we suggest both the use of the neuronavigation technique and of the indocyanine green videoangiography (ICGV) for the aneurismal surgery.